Tuck everlasting - Babbitt, Natalie 1932-2016 (Farrar, Straus, Giroux, 1987)
From the Publisher: Is eternal life a blessing or a curse? That is what young Winnie Foster must decide when she discovers a spring on her family's property whose waters grant immortality. Members of the Tuck family, having drunk from the spring, tell Winnie of their experiences watching life go by and never growing older. But then Winnie must decide whether or not to keep the Tucks' secret-and whether or not to join them on their never-ending journey